2020
DOI: 10.1002/fsn3.1486
|View full text |Cite
|
Sign up to set email alerts
|

The physicochemical properties of chitosan prepared by microwave heating

Abstract: The aim of this study was to compare the physicochemical properties of chitosan prepared by microwave and water bath heating with an equivalent quantity of heat intake. The structure and physicochemical properties of the chitosan obtained by these two methods were characterized by Fourier transform infrared spectroscopy (FTIR), X‐ray diffractometry (XRD), gel permeation chromatography (GPC), and scanning electron microscopy (SEM). The FTIR and XRD patterns show that there was no significant difference in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…XRD spectra revealed that the addition of GO within the GCs matrix seems to cause alterations [ 2 ] within the unmodified samples spectrum, as the 11.7° peak associated with chitosan’s crystal I [ 93 ] and 21° band paired to the crystal II structure [ 94 ] significantly sharpen. Hence, it can be assumed that the identified sharpening is associated with a higher degree of crystallinity of the polysaccharide [ 95 ]; crystallization firstly occurred after crosslinking and accelerated with the GO embedding [ 30 ] within the matrix. This is confirmed by the crystallinity index (CI) that resulted from CI = [(I cr − I am )/I110] × 100, where I cr is the maximum intensity of the diffraction peak of Cs, and I am is the intensity of amorphous diffraction at 2θ = 16° [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…XRD spectra revealed that the addition of GO within the GCs matrix seems to cause alterations [ 2 ] within the unmodified samples spectrum, as the 11.7° peak associated with chitosan’s crystal I [ 93 ] and 21° band paired to the crystal II structure [ 94 ] significantly sharpen. Hence, it can be assumed that the identified sharpening is associated with a higher degree of crystallinity of the polysaccharide [ 95 ]; crystallization firstly occurred after crosslinking and accelerated with the GO embedding [ 30 ] within the matrix. This is confirmed by the crystallinity index (CI) that resulted from CI = [(I cr − I am )/I110] × 100, where I cr is the maximum intensity of the diffraction peak of Cs, and I am is the intensity of amorphous diffraction at 2θ = 16° [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cheng et al [ 70 ] reported physicochemical properties of chitosan prepared by microwave and water bath heating with an equivalent quantity of heat intake. Briefly, chitosan production with microwave heating reduced the time of deacetylation from 180 to 60 min to reach the same DD% as the water bath heating with the same quantity of heat.…”
Section: Chitosan As a Matrix For Nanosystemspreparation: Methodsmentioning
confidence: 99%
“…In addition to the faster reaction rates and energy saving procedures MAOS represents a green, cheap, and easy chemistry 17 with less side reactions or generation of toxic products 18 ; all features essentials when functionalization reaction are exploited aiming at biomedical applications. Several studies confirmed the MAOS efficacy and convenience, even in the biological field 19,20 , but less efforts were put in the synthesis and functionalization of natural polymers 21,22 for biomedical applications 23 . Chitosan is a natural polysaccharide produced by partial deacetylation of chitin, which is a component of crab/shrimp shells and the second most abundant polysaccharide on the earth, after cellulose.…”
Section: Introductionmentioning
confidence: 99%